CRITICAL ANALYSIS OF THE CONSTITUTIONAL STATE AND CONTEMPORARY TRANSNATIONALISM (Interdisciplinary Studies Journal, 2025)
Abstract: Access to justice is a fundamental right that ensures all citizens can resolve conflicts and exercise their rights equitably and efficiently. This article aimed to critically analyze key aspects of access to justice (in a broad sense) in the contemporary scenario, with a focus on the convergence between civil law and common law systems, as well as the impact of new technologies such as artificial intelligence (AI) and Online Dispute Resolution (ODR) platforms. The research adopted a qualitative and exploratory approach, based on a bibliographic review, documentary analysis, and comparative analysis, using academic databases such as SciELO and Google Scholar. Recent and relevant works were selected with quality and geographic scope criteria to ensure the depth and timeliness of the debate.The comparative analysis of legal systems highlighted the characteristics of mixed jurisdictions, such as Quebec and Louisiana, while the interdisciplinary approach integrated insights from Law, Technology, and Sociology to discuss the impact of digitalization on access to justice. The article also provides critical reflections on judicialization, dejudicialization, judicial activism, and self-restraint, along with projections for the future of access to justice, considering technological advancements and social changes. As a contribution, the study suggests the creation of ethical guidelines for the use of AI in the judiciary, public policies for digital inclusion, and the promotion of alternative dispute resolution methods. It concludes that the convergence between legal systems and the adoption of technologies can expand access to justice, but requires ethical and legal considerations to ensure effectiveness and equity.Keywords: Constitutional State; Sovereignty;Transnationalism; Environmental Protection..
Keywords: Public Administration